Green tea extract and its major constituent epigallocatechin-3-gallate inhibit growth and halitosis-related properties of Solobacterium moorei - Morin, Marie-Pierre; Bedran, Telma Blanca Lombardo [UNESP]; Fournier-Larente, Jade; Haas, Bruno; Azelmat, Jabrane; Grenier, Daniel (Biomed Central Ltd, 2015)
Background: Solobacterium moorei is a volatile sulfide compound (VSC)-producing Gram-positive anaerobic bacterium that has been associated with halitosis. The aim of this study was to investigate the effects of green tea extract and its major constituent epigallocatechin-3-gallate (EGCG) on growth and severalhalitosis-related properties of S. moorei.Methods: A microplate dilution assay was used to determine the antibacterial activity of green tea extract and EGCG against S. moorei. Their effects on bacterial cell membrane integrity were investigated by transmission electron microscopy and a fluorescence-based permeability assay. Biofilm formation was quantified by crystal violet staining. Adhesion of FITC-labeled S. moorei to oral epithelial cells was monitored by fluorometry. The modulation of beta-galactosidase gene expression in S. moorei was evaluated by quantitative RT-PCR.Results: The green tea extract as well as EGCG inhibited the growth of S. moorei, with MIC values of 500 and 250 mu g/ml, respectively. Transmission electron microscopy analysis and a permeabilization assay brought evidence that the bacterial cell membrane was the target of green tea polyphenols. Regarding the effects of green tea polyphenols on the S. moorei colonization properties, it was found that biofilm formation on EGCG-treated surfaces was significantly affected, and that green tea extract and EGCG can cause the eradication of pre-formed S. moorei biofilms. Moreover, both the green tea extract and EGCG were found to reduce the adherence of S. moorei to oral epithelial cells. The beta-galactosidase activity of S. moorei, which plays a key role in VSC production, was dose-dependently inhibited by green tea polyphenols. In addition, EGCG at 1/2 MIC significantly decreased the beta-galactosidase gene expression.Conclusion: Our study brought evidence to support that green tea polyphenols possess a number of properties that may contribute to reduce S. moorei-related halitosis. Therefore, these natural compounds may be of interest to be used to supplement oral healthcare products.
Keywords: Green tea; EGCG; Halitosis; Solobacterium moorei